The NLRP3 inflammasome contributes to inflammation‐induced morphological and metabolic alterations in skeletal muscle. Issue 6 (17th August 2022) - Eggelbusch, Moritz; Shi, Andi; Broeksma, Bonnie C.; Vázquez‐Cruz, Mariana; Soares, Madu N.; de Wit, Gerard M. J.; Everts, Bart; Jaspers, Richard T.; Wüst, Rob C.I.
Abstract: Background: Systemic inflammation is associated with skeletal muscle atrophy and metabolic dysfunction. Although the nucleotide‐binding oligomerization domain‐like receptor family pyrin domain containing 3 (NLRP3) inflammasome contributes to cytokine production in immune cells, its role in skeletal muscle is poorly understood. Here, we studied the link between inflammation, NLRP3, muscle morphology, and metabolism in in vitro cultured C2C12 myotubes, independent of immune cell involvement. Methods: Differentiated C2C12 myotubes were treated with lipopolysaccharide (LPS; 0, 10, and 100–200 ng/mL) to induce activation of the NLRP3 inflammasome with and without MCC950, a pharmacological inhibitor of NLRP3‐induced IL‐1β production. We assessed markers of the NLRP3 inflammasome, cell diameter, reactive oxygen species, and mitochondrial function. Results: NLRP3 gene expression and protein concentrations increased in a time‐dependent and dose‐dependent manner. Intracellular IL‐1β concentration significantly increased ( P < 0.0001), but significantly less with MCC950 ( P = 0.03), suggestive of moderate activation of the NLRP3 inflammasome in cultured myotubes upon LPS stimulation. LPS suppressed myotube growth after 24 h ( P = 0.03), and myotubes remained smaller up to 72 h ( P = 0.0009). Exposure of myotubes to IL‐1β caused similar alterations in cell morphology, and MCC950 mitigated these LPS‐induced differences in cell diameter. NLRP3 appeared to co‐localize with mitochondria, more so upon exposure to LPS. Mitochondrial reactive oxygen species were higher after LPS ( P = 0.03), but not after addition of MCC950. Myotubes had higher glycolytic rates, and mitochondria were more fragmented upon LPS exposure, which was not altered by MCC950 supplementation. Conclusions: LPS‐induced activation of the NLRP3 inflammasome in cultured myotubes contributes to morphological and metabolic alterations, likely due to its mitochondrial association.